Effects of sustainable land management interventions on selected soil properties in Geda watershed, central highlands of Ethiopia - Terefe, Hailu; Argaw, Mekuria; Tamene, Lulseged D.; Mekonnen, Kindu; Recha, John W.M.; Solomon, Dawit (Springer, 2020)
Land degradation through soil erosion by water is severe in the highlands of Ethiopia. In order to curb this problem, the government initiated sustainable land management interventions in different parts of the country since 2008, and in Geda watershed since 2012. However, the impacts of the interventions on soil properties were not assessed so far. Thus, this study investigated the impacts of sustainable land management interventions on selected soil properties in Geda watershed. Soil samples were collected from treated and untreated sub-watersheds at the upper and lower landscape positions, from cropland and grazing lands at two soil depths (0–15 cm and 15–30 cm). Selected soil physicochemical properties were assessed with respect to landscape position, land-use type, and soil depth in both treated and untreated sub-watersheds.Generally, most of the soil physicochemical properties differed greatly across sub-watersheds, land-use types, and soil depths. Clay, electrical conductivity, total N, available P, exchangeable K, and organic carbon were higher in the treated sub-watershed, whereas sand, silt, bulk density, and pH were higher in the untreated sub-watershed. The higher sand, silt, and bulk density could be attributed to erosion, while the higher pH could be due to the higher exchangeable Na in the untreated sub-watershed. Most of the selected soil chemical properties were not affected by landscape position, but land-use type affected available P and organic carbon with higher mean values at croplands than at grazing lands, which could be ascribed to the conservation structure and tillage of the soils in that conservation structures trap and accumulate transported organic materials from the upper slope, while tillage facilitates aeration and decomposition processes.Sustainable land management interventions improved soil physicochemical properties and brought a positive restoration of the soil ecosystem. Maintaining the soil conservation measures and enhancing community awareness about the benefits, coupled with management of livestock grazing are required to sustain best practices.